Motivation of Employee Cooperative Members in Increasing Income : A Case Study on the Employee Cooperative of PT. Independent Premier Eagle - Supriyanto; Sofyan, Mohammad (CV ODIS, 2024)
This study aims to find out and analyze the motivation of Kopkar members of PT. Elang Perdana Mandiri by exploring the desires, roles, and benefits of employee cooperative members in improving the welfare of members and how joint efforts in the cooperative create a better future; in this scientific paper, I take the example of one of the employee cooperatives in the Citeureup sub-district area, Bogor Regency, namely the PT Elang Perdana Mandiri Employee Cooperative, considering that employee cooperatives have become a growing phenomenon in various industries and is expected to be a model of multiple ownership and participation of members in decision-making of Cooperative Organizations. We use a study approach by applying a qualitative method by conducting field observations and direct interviews with several parties who are directly involved in the employee cooperative; the employee cooperative of PT Elang Perdana Mandiri has succeeded in creating financial sustainability, improving the welfare of its members, and motivating them to take an active role in the management of the PT Elang Perdana Mandiri Employee Cooperative organization. Through interviews, surveys, and data analysis, a strategy and practice used by this cooperative to advance PT Elang Perdana Mandiri Kopkar was obtained. From the data on the number of 868 members, active members participated in the savings and loan unit as many as 662 people (76.3%), active transactions at stores as many as 644 people (76.2%), while members who saved in cooperatives as many as 721 people (83%) with a total deposit of IDR 2,460,187,998, - or 10.9% of the total assets owned by the cooperative as of September 2023 amounted to IDR 22,604,914,808,-. The results of the study show that through the active participation of cooperative members, skill development and promotion of cooperation and education are the primary targets to improve knowledge and skills not only for managers but also for members' insights into cooperative organization activities so that they members are increasingly committed to maintaining, developing, and utilizing cooperatives as a forum to carve hope towards prosperity. The motivation of members to do entrepreneurship and cooperate with cooperatives is still relatively high. The data of members who collaborate with cooperatives currently consists of cooperation in selling MSE products, with as many as 32 members (4%) of the total members, which made the author conduct research. The findings of this study provide valuable insights for other cooperative organizations that want to implement the employee cooperative model to create brighter expectations in the future.